Cierre percutáneo de la auriculilla izquierda con dispositivo Watchman: opción para pacientes con fibrilación auricular y alto riesgo de sangrado por anticoagulación (2015)
ABSTRACT: Atrial fibrillation is the most common arrhythmia found in clinical practice, with a population prevalence of 1% to 2%. Anticoagulation remains a fundamental part of treatment for the prevention of cerebrovascular events (stroke), but it is contraindicated in approximately 20% of patients. We report a case of non-valvular atrial fibrillation with high-risk score for stroke, a history of intracerebral bleeding, and very high risk of bleeding with long-term anticoagulation. Percutaneous closure of the left atrial appendage with the Watchman device was performed successfully without complications.